An efficiency comparison of different in vitro fertilization methods: IVF, ICSI, and PICSI for embryo development to the blastocyst stage from vitrified porcine immature oocytes - Casillas, Fahiel (Porcine Health Manag, 2018)
BACKGROUND: Most studies carried out to evaluate recovery and development after porcine oocyte vitrification, reported better rates when cryopreserved in embryonic development stages or zygotes, but not in immature oocytes. For this reason, many studies are performed to improve immature oocyte vitrification protocols testing the use of different cryoprotectant concentrations, cooling devices, incubation times; but only a few of them have evaluated which fertilization procedure enhances blastocyst rates in vitrified oocytes. Therefore, this study was aimed to evaluate: 1) if the sperm selection with hyaluronic acid (HA) or polyvinylpyrrolidone (PVP) before injection could play a key role in increasing fertilization and blastocyst formation and 2) the embryo developmental ability and blastocyst production of porcine immature oocytes retrieved after vitrification-warming and co-cultured with granulosa cells during IVM, using different fertilization techniques: in vitro fertilization (IVF), intracytoplasmic sperm injection (ICSI) and conventional ICSI with hyaluronic acid (HA) sperm selection, known as physiological intracytoplasmic sperm injection (PICSI) and. RESULTS: Sperm selected with HA-PICSI displayed a higher percentage of live/acrosome reacted status compared to those in control and exposed to PVP. Higher dead/acrosome reacted rates were obtained after PVP exposure compared to control and HA. In oocytes, viability significantly decreased after IVM in vitrified oocytes. Besides, IVM rates were not different between control denuded oocytes cultured with granulosa cells (DO-GC) and vitrified oocytes. Regarding fertilization parameters, IVF showed higher percentages of total fertilization rate than those obtained by ICSI and PICSI. However, results demonstrate that PICSI fertilization increased the blastocysts formation rate in control DO-GC and vitrified oocytes compared to IVF and ICSI. CONCLUSIONS: To achieve high blastocyst formation rates from vitrified GV oocytes, it is recommended that sperm should be selected with HA instead of PVP before injection since high viability and acrosome reaction rates were obtained. Also, PICSI fertilization was the best method to produce higher blastocyst rates compared to the IVF and ICSI procedures.